PENGARUH BERBAGAI DOSIS KOMPOS SLUDGE LIMBAH PKS TERHADAP PERTUMBUHAN DAN PRODUKSI PADI (Oryza sativa L.) DENGAN METODE SRI - Zulni, Mega; Effendi, Arman; Zulfatri, Zulfatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The aim of this research is to find out the influence of composting sludge of PKS waste and to obtain optimum dose for rice growth and production                   (Oryza sativa L.) through SRI methodology. The experiment was conducted in an experimental field of Faculty of Agriculture, Riau University, in June until September  2018. The experiment was conducted by experiment using completely randomized design (CRD) through using of sludge compost, the sludge compost consist of 5 treatments ; 0 t.ha-1, 10 t.ha-1, 15 t.ha-1, 20 t.ha-1 and 25 t.ha-1 using SRI methodology it where watertable was 10 centimeters below ground level. The observed parameters were: plant height, growth of plants, rapid of net assimilation, ratio of the root canopy, tillers maximum number, number of productive tillers, age of panicles, panicle length, harvest age, number of rice grain per panicle, number of rice grain per hill,percentage of unripe rice per hill, weight of 1000 grain of pithy rice and weight of dried grain per clump.The results obtained in the analysis using Duncan New Multiple Range Test (DNMRT) at 5%. The result of this research show that composting of sludge compost of         20 t.ha-1 using SRI methodology where watertable was 10 cm below ground level gave best result for LPT, LAB, tillers maximum number, number of productive tillers, panicle length, number of rice grain per hill and weight of dried grain per clump. Keywords: SRI methodology, sludge, rice